2001
DOI: 10.1046/j.0269-283x.2001.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Old World screwworm fly, Chrysomya bezziana, occurs as two geographical races

Abstract: A morphological and molecular analysis was undertaken with the objective of identifying markers for geographical populations of Old World screwworm flies, Chrysomya bezziana Villeneuve (Diptera: Calliphoridae). The morphological analysis involved 192 adult flies from 14 countries, and the molecular analysis involved 45 larvae or adults from 14 populations in 11 countries. Principal components and cluster analysis of 10 morphological characters indicated that flies from Papua New Guinea (PNG) were a distinct gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 14 publications
1
39
1
1
Order By: Relevance
“…Geographically, this fly is widely distributed in Africa, the Middle East, the Indian subcontinent, south-eastern Asia, and Australia (Mahon et al 2004) and was recently recorded as an insect involved in parasitic zoonoses in Papua New Guinea (Owen 2005). Morphological and molecular analyses of C. bezziana populations by Hall et al (2001) has revealed that there are two races of this fly species, one from sub-Saharan Africa and the other from the Gulf region and Asia.…”
Section: Introductionmentioning
confidence: 98%
“…Geographically, this fly is widely distributed in Africa, the Middle East, the Indian subcontinent, south-eastern Asia, and Australia (Mahon et al 2004) and was recently recorded as an insect involved in parasitic zoonoses in Papua New Guinea (Owen 2005). Morphological and molecular analyses of C. bezziana populations by Hall et al (2001) has revealed that there are two races of this fly species, one from sub-Saharan Africa and the other from the Gulf region and Asia.…”
Section: Introductionmentioning
confidence: 98%
“…Cutaneous myiasis caused by the Old World screw-worm fly, Chrysomya bezziana, is a wide spread infestation of domestic animals and man in Southeast Asian and African countries (Soulsby 1982;Hall et al 2001;Mahon et al 2004). Chrysomya bezziana is an obligatory parasite of warm blood animals, lays eggs in necrotic tissues and/or wounds caused by ticks and lice which offer a favourable environment for the development of their larvae.…”
Section: Introductionmentioning
confidence: 99%
“…This screwworm species is also found in tropical and subtropical sub-Saharan Africa, and in several countries in the Middle East (Spradbery 2002). Kloft et al (1981) reported repeated "transit infestations" of the Old World screwworm from South-East Asia to the Middle East, and a recent (1996) infestation recorded in Iraq is assumed to have originated from South-East Asia (Hall et al 2001). …”
Section: Potential Old World Screwworm Programmesmentioning
confidence: 96%
“…Before an eradication programme is planned, however, an essential preliminary phase is the collection of comprehensive baseline data, including ecological and genetic studies to delineate the relevance of the problem (Hall et al 2001 …”
Section: Preparatory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation